Nos fundos da sociabilidade: usos e funções dos quintais populares paulistanos no final do século XIX e início do XX - Lucchesi, Bianca Melzi De Domenicis (2021)
This work aims to analyze the uses and functions of backyards in the formation of sociability of the popular classes in São Paulo, as well as their representation in urban and rural aspects that coexist in the capital of São Paulo in the late nineteenth and early twentieth centuries. The backyard takes on domestic, economic, leisure and house maintenance functions, in addition to representing a universe of cultural expression. The studied iconography and different modalities of claims envisioned the backyard as a space of tension, whether in its relationship with the street, making the concepts of public and private subjective, or through questioning, requests and arguments exposed by the residents in relation to rights and assessments involving the backyard. The period comprising this research encompasses important political, social and structural changes in the city of São Paulo. Even though backyards are just a housing environment and a small particle within the city, it is important to consider how their configuration, functions and roles are changed or adapted in the midst of modernization and densification of the city. Thus, the research covers the changes related to the backyard of low-income housing through legislation that reflects the urban transformations of São Paulo at the time described